A User-Friendly Dynamic Reactor Simulator Built in Microsoft Excel - Chew Hernandez, M. L.; Viveros Rosas, L.; Hernandez-Arrieta, I. (Engineering, Technology & Applied Science Research, 2022)
Computer plant simulation is being used in all aspects of engineering, through many simulation software packages. However, almost all of them require licenses that must be purchased by engineering colleges intending to use simulation in their teaching. As public educational institutions everywhere are facing a scarcity of economic resources, they can resort to a freeware steady-state plant simulator, however, there is no availability of reliable, free dynamic plant simulators. In addition, published experiences on developing dynamic simulators use programming languages requiring paid licenses (e.g. Matlab) and thus have limited relevancy to schools struggling to cut expenses. This article first uses a set of typical college objectives to discuss the advantages of building their own dynamic simulators, and then shows the development of a user-friendly dynamic simulator of a batch reactor constructed entirely within Microsoft Excel, which, in contrast to the programming languages used in related reports, is already widely used by universities around the world.